ANALISIS PENGGUNAAN STEM TERINTEGRASI SDGs DALAM PEMBELAJARAN DI INDONESIA: SYSTEMATIC LITERATURE REVIEW - Fabrizia Hidayatul Fadilla; Nurul Mahmudah; Joaquin Iqlima Ramadhani; Litahayu Athresia Lutfi; Amelia Amelini (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This study investigates the implementation of STEM education integrated with the Sustainable Development Goals (SDGs) across various educational levels in Indonesia. It examines the approach’s impact on students as well as the practical challenges faced in classroom settings. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 protocol. Literature was retrieved from the Crossref database via Publish or Perish for the period 2021–2025. From 100 identified articles, only eight met the inclusion criteria and were thoroughly analyzed. The results show that STEM-SDG integration in Indonesia is predominantly implemented through interactive e-modules and project-based worksheets (LKPD). The most frequently incorporated goals are SDG 4, 7, 12, and 13, although several studies also applied STEM as complete learning models. Overall, the integrated approach effectively improved students’ environmental literacy, ecological awareness, and science learning outcomes. However, gains were inconsistent, particularly in scientific communication skills and appropriate use of scientific language. Most studies remain at the developmental stage, with limited robust experimental evidence on effectiveness. While STEM-SDG integration shows strong potential in fostering a sustainability-minded generation, significant research gaps persist in terms of educational levels, breadth of SDGs covered, and variety of outcome variables. ABSTRAK Penelitian ini mengkaji bagaimana pendekatan STEM yang diintegrasikan dengan Sustainable Development Goals (SDGs) diterapkan dalam pembelajaran di Indonesia, baik dari segi dampaknya bagi peserta didik maupun hambatan apa saja yang ditemui di lapangan. Penelitian ini dilakukan menggunakan pendekatan Systematic Literature Review (SLR) beracuan pada protokol PRISMA 2020. Literatur didapatkan melalui database Crossref berbantuan Publish or Perish dalam rentang tahun 2021–2025. Dari 100 artikel yang ditemukan, 8 artikel memenuhi kriteria inklusi dan dianalisis secara mendalam. Hasil kajian menunjukkan bahwa integrasi STEM-SDGs di Indonesia paling banyak diwujudkan melalui pengembangan e-modul interaktif dan LKPD berbasis proyek, dengan SDG 4, 7, 12, dan 13 sebagai tujuan yang paling sering diangkat dalam konteks pembelajaran. Namun, penerapan pendekatan STEM dalam bentuk model pembelajaran juga ditemukan. Secara umum, pendekatan ini berhasil meningkatkan literasi lingkungan, kesadaran ekologis, dan hasil belajar IPA peserta didik, meskipun peningkatan tidak merata pada semua aspek, terutama pada keterampilan komunikasi ilmiah dan penggunaan bahasa sains yang tepat. Sebagian besar penelitian masih bertumpu pada model pengembangan, sehingga bukti efektivitas dari desain eksperimen yang kuat masih terbatas. Integrasi STEM-SDGs menyimpan potensi besar dalam membentuk generasi yang berwawasan keberlanjutan, namun masih banyak celah penelitian yang perlu diisi, baik dari sisi jenjang pendidikan, cakupan SDGs, maupun keragaman variabel yang dikaji.